2017
DOI: 10.1007/s11356-017-9865-9
|View full text |Cite
|
Sign up to set email alerts
|

The dissipation and risk assessment of 2,4-D sodium, a preharvest anti-fruit-drop plant hormone in bayberries

Abstract: Preharvest fruit-drop is a challenge to bayberry production. 2,4-D sodium as a commonly used anti-fruit-drop hormone on bayberry can reduce the yield loss caused by preharvest fruit-drop. The persistence and risk assessment of 2,4-D sodium after applying on bayberries were investigated. A method for determining 2,4-D sodium in bayberry was established based on LC-MS-MS. The average recoveries of 2,4-D sodium were at the range of 93.7-95.8% with relative standard deviations (RSDs) ranging from 0.9 to 2.8%. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…2,4-D has been widely used on cucumber in China since 2007 [16] for two major purposes: (1) to produce cucumber fruits with a flesh flower on top, making the cucumbers more attractive to customers; (2) to promote the fruit setting rate and the fruit growth of parthenocarpic cucumber cultivars in greenhouses where bees are excluded. In one of our previous studies, we detected residual 2,4-D in 1674 batches of vegetables (including cucumber), fruits and crops from grocery stores and evaluated the 2,4-D dietary exposure risk in China [17]. The results indicated that the 2,4-D levels in both acute and chronic dietary exposures were significantly lower than the acceptable reference dose, implying that the risk of dietary exposure to 2,4-D was quite low, not reaching a health concern level [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,4-D has been widely used on cucumber in China since 2007 [16] for two major purposes: (1) to produce cucumber fruits with a flesh flower on top, making the cucumbers more attractive to customers; (2) to promote the fruit setting rate and the fruit growth of parthenocarpic cucumber cultivars in greenhouses where bees are excluded. In one of our previous studies, we detected residual 2,4-D in 1674 batches of vegetables (including cucumber), fruits and crops from grocery stores and evaluated the 2,4-D dietary exposure risk in China [17]. The results indicated that the 2,4-D levels in both acute and chronic dietary exposures were significantly lower than the acceptable reference dose, implying that the risk of dietary exposure to 2,4-D was quite low, not reaching a health concern level [17].…”
Section: Introductionmentioning
confidence: 99%
“…In one of our previous studies, we detected residual 2,4-D in 1674 batches of vegetables (including cucumber), fruits and crops from grocery stores and evaluated the 2,4-D dietary exposure risk in China [17]. The results indicated that the 2,4-D levels in both acute and chronic dietary exposures were significantly lower than the acceptable reference dose, implying that the risk of dietary exposure to 2,4-D was quite low, not reaching a health concern level [17]. A water rinsing of 2,4-D sodium treated fruits for one minute can remove half of the 2,4-D sodium residue [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation